2021
DOI: 10.1007/s10209-021-00840-0
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the utility of digital materials for high school students with intellectual disability and their effects on academic success

Abstract: This study thoroughly examines the usability of digital materials, to establish a classroom environment in which technology is integrated into teaching practices using tablet computers and interactive smart boards. The study was conducted at a special education vocational school, where students with intellectual disability receive training. The integration of technology was made to the Natural Disasters unit (erosion, landslide, flood, earthquake, and digital story developed on the subject of flood) in the Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Mobile applications [14], [15], [16], [17], [18], [19], [20], [21], [22], [23] Augmented reality [24], [25], [26], [27], [28], [29] Digital tools [30], [31], [32], [33] Web applications [34], [35], [36], [37], [38], [39], [40], [41], [42] Desktop applications [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55],…”
Section: Category Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile applications [14], [15], [16], [17], [18], [19], [20], [21], [22], [23] Augmented reality [24], [25], [26], [27], [28], [29] Digital tools [30], [31], [32], [33] Web applications [34], [35], [36], [37], [38], [39], [40], [41], [42] Desktop applications [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55],…”
Section: Category Articlesmentioning
confidence: 99%
“…[34], [35], [36], [37], [38], [39], [40], [41], [42] These articles argue that the usability of digital technologies increases learning competencies in students where the interaction of the student with different applications is seen.…”
Section: Themes and Functionality Referencesmentioning
confidence: 99%
“…These results represent different learning stages of the learning experience modes. The differences between each pair of results reflect the scores of different style dimensions, and quadrants were formed using the numerical values across different dimensions [9,10]. The detailed division results are listed as follows:…”
Section: Analysis Of Vocational Education Teaching Practicesmentioning
confidence: 99%
“…Given the evolving nature of computer programming from machine language to object‐oriented programming using different programming languages like Javascript, C, C++, Python among others, the understanding of such emerging trends like machine learning [66], artificially intelligent [162] and robotics programming [7], among others have a significant effect on the learning content and teaching strategies employed. Studies have shown that teaching methods applied in teaching programming are a determinant of learners' interest [18], academic success [46], engagement [105], enrolment [15], among others. Other studies posit that poor teaching methods and strategies could be attributed to the continuous decline in student enrolment in the computer programming discipline among other factors leading to persistent low performance in computer programming.…”
Section: Introductionmentioning
confidence: 99%